Corrigendum for: Sex Differences in Blood Pressure, Free Radicals and Plasma Cholesterol Fractions in Ren-2 Transgenic Rats of Various Ages - Rauchová, Hana; Hojná, Silvie; Kadlecová, Michaela; Vaněčková, Ivana; Chao, Y-M; Chan, J Yh; Zicha, Josef (Physiological research, 2023)
List of changes: On the basis of author's request the publisher of Physiological Research decided to change the license of the article to CC BY license.